Climate and crown damage drive tree mortality in southern Amazonian edge forests - Reis, Simone M.; Marimon, Beatriz S.; Esquivel‐Muelbert, Adriane; Marimon, Ben Hur; Morandi, Paulo S.; Elias, Fernando; Oliveira, Edmar A.; Galbraith, David; Feldpausch, Ted R.; Menor, Imma O.; Malhi, Yadvinder; Phillips, Oliver L. (The Journal of ecology, 2022)
Tree death is a key process for our understanding of how forests are and will respond to global change. The extensive forests across the southern Amazonia edge—the driest, warmest and most fragmented of the Amazon regions—provide a window onto what the future of large parts of Amazonia may look like. Understanding tree mortality and its drivers here is essential to anticipate the process across other parts of the basin. Using 10 years of data from a widespread network of long‐term forest plots, we assessed how trees die (standing, broken or uprooted) and used generalised mixed‐effect models to explore the contribution of plot‐, species‐ and tree‐level factors to the likelihood of tree death. Most trees died from stem breakage (54%); a smaller proportion died standing (41%), while very few were uprooted (5%). The mortality rate for standing dead trees was greatest in forests subject to the most intense dry seasons. While trees with the crown more exposed to light were more prone to death from mechanical damage, trees less exposed were more susceptible to death from drought. At the species level, mortality rates were lowest for those species with the greatest wood density. At the individual tree level, physical damage to the crown via branch breakage was the strongest predictor of tree death. Synthesis. Wind‐ and water deficit‐driven disturbances are the main causes of tree death in southern Amazonia edge which is concerning considering the predicted increase in seasonality for Amazonia, especially at the edge. Tree mortality here is greater than any in other Amazonian region, thus any increase in mortality here may represent a tipping point for these forests. Resumo A mortalidade de árvores é um processo fundamental para nossa compreensão de como as florestas são e como responderão às mudanças climáticas globais. As florestas ao longo da extensa borda sul da Amazônia—a mais seca, quente e fragmentada das regiões amazônicas—são uma janela para o futuro de outras partes da Amazônia. Compreender a mortalidade das árvores e seus fatores aqui é essencial para antecipar o processo em outras partes da bacia. Usando 10 anos de dados de uma ampla rede de parcelas florestais de longo prazo, avaliamos como as árvores morrem (em pé, quebradas ou desenraizadas) e usamos modelos generalizados de efeitos mistos para explorar a contribuição de fatores ao nível de parcelas, espécies e árvores para o risco de morte de árvores. A maioria das árvores morreu quebrada (54%); uma proporção menor morreu em pé (41%), enquanto poucas morreram desenraizadas (5%). A taxa de mortalidade para árvores mortas em pé foi maior em florestas sujeitas a intensa sazonalidade e secas mais intensas. Enquanto as árvores com copa mais exposta à luz eram mais propensas à morte por danos mecânicos, as árvores menos iluminadas eram mais suscetíveis à morte por seca. Ao nível de espécie, as taxas de mortalidade foram mais baixas para as espécies com maior densidade de madeira. Ao nível da árvore, o dano físico à copa por meio da quebra de galhos na copa foi o preditor mais importante da morte de árvores. Síntese. Perturbações causadas pelo déficit de água e vento são as principais causas de morte de árvores na borda sul da Amazônia, o que é preocupante, considerando o prolongamento previsto na sazonalidade para a Amazônia, especialmente na borda sul. A mortalidade de árvores aqui é maior do que em qualquer outra região amazônica, portanto, qualquer aumento na mortalidade pode representar um ponto de inflexão “não retorno” para essas florestas. Tree death is a key process for our understanding of how forests are responding to global change. Our long‐term research shows that more than 70% of all trees dying in this critical region at the edge of Amazonia already had markedly broken and damaged crowns years before they died. The damage caused by climate extremes—especially wind and drought—is concerning in light of widespread increases in dry‐season intensity in the Amazon, and as tree mortality is already greater here than any in other Amazonian region, increases in mortality here may herald a tipping point for these forests.